Introduction to Intelligent Transportation Systems - Alam, Muhammad
Transportation systems are very important in modern life; therefore, massive research efforts has been devoted to this field of study in the recent past. Effective vehicular connectivity techniques can significantly enhance efficiency of travel, reduce traffic incidents and improve safety, alleviate the impact of conges- tion; devising the so-called Intelligent Transportation Systems (ITS) experience. This chapter aims to provide basic concepts and background that is useful for the understanding of this book. An overview of intelligent transportation systems and their applications is presented, followed by a brief discussion of vehicular com- munications. The chapter also overviews the concepts related to dependability on distributed real-time systems in the scope if ITS.